2017
DOI: 10.1080/2162402x.2017.1317420
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 restricts tumor growth and inhibits pulmonary metastasis in melanoma-bearing mice through eosinophils

Abstract: The alarmin IL-33 is an IL-1 family member that stimulates pleiotropic immune reactions depending on the target tissue and microenvironmental factors. In this study, we have investigated the role of IL-33/ST2 axis in antitumor response to melanoma. Injection of IL-33 in mice-bearing subcutaneous B16.F10 melanoma resulted in significant tumor growth delay. This effect was associated with intratumoral accumulation of CD8 T cells and eosinophils, decrease of immunosuppressive myeloid cells, and a mixed Th1/Th2 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
191
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(204 citation statements)
references
References 61 publications
10
191
3
Order By: Relevance
“…Therefore, the suppressing effect on tumor growth, which we observed, may be related, in part, to the presence of eosinophils. Concordantly with this hypothesis, Lucarini et al (2017) reported that both B16F10 melanoma growth and metastasis formation were enhanced upon in vivo depletion of eosinophils using an anti-Siglec-F antibody. Eosinophils have also been found to enable T cell responses through the normalization of the tumor vasculature (Carretero et al, 2016).…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, the suppressing effect on tumor growth, which we observed, may be related, in part, to the presence of eosinophils. Concordantly with this hypothesis, Lucarini et al (2017) reported that both B16F10 melanoma growth and metastasis formation were enhanced upon in vivo depletion of eosinophils using an anti-Siglec-F antibody. Eosinophils have also been found to enable T cell responses through the normalization of the tumor vasculature (Carretero et al, 2016).…”
Section: Discussionsupporting
confidence: 59%
“…Given the important role of NK cells in inhibiting the growth of metastatic tumor in mouse model, we explored whether IL‐33 inhibited the development of metastatic tumor in 4T1‐Luc mouse model in an NK cell‐dependent manner. By depleting NK cells using an anti‐AsGM1 antibody (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the important role of NK cells in inhibiting the growth of metastatic tumor in mouse model, 23 we explored whether Fig. S4a), the tumor growth inhibitory activity of IL-33 was completely abolished (Fig.…”
Section: Nk Cells Play a Dominant Role In The Il-33-mediated Suppressmentioning
confidence: 99%
See 1 more Smart Citation
“…Many endothelial cells and tumors express both ST2L and sST2 mRNA [15, 16]. A large body of data has confirmed that the IL-33/ST2 axis affects the progression of many tumors, either through regulation of the immune system or by acting directly on tumor cells [17-23]. …”
Section: Introductionmentioning
confidence: 99%